2014
DOI: 10.1016/j.landusepol.2014.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dutch planning policy: The resurgence of TOD

Abstract: a b s t r a c tThis article examines the transfer of knowledge and information in planning processes, particularly those related to Transit-Oriented Development (TOD) in the metropolitan region of Amsterdam. The authors conclude that knowledge transfers are often highly dependent on the actions of individuals, and that the process of knowledge exchange is frequently uncoordinated and fragmented. Planning ideas from elsewhere often provide inspiration for policy makers but these do not often lead to changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…With the ambition to become the second largest economic area in the Netherlands after Randstad by 2020, the city region aims to promote regional cooperation (ArnhemNijmegen City Region, 2018). It is esteemed to be one of the beacons of TOD in the Netherlands (Pojani & Stead, 2014). It is also considered representative of other European regions of similar scale that are pursuing TOD.…”
Section: Study Areamentioning
confidence: 99%
“…With the ambition to become the second largest economic area in the Netherlands after Randstad by 2020, the city region aims to promote regional cooperation (ArnhemNijmegen City Region, 2018). It is esteemed to be one of the beacons of TOD in the Netherlands (Pojani & Stead, 2014). It is also considered representative of other European regions of similar scale that are pursuing TOD.…”
Section: Study Areamentioning
confidence: 99%
“…Although a highly knowledgeable "TOD lobby" has formed, it has failed to reach a wider audience and frame the TOD concept for the planning community. Local planners are searching for (a) ideas related to the urban design of areas in the immediate proximity of train stations, and (b) financial tools that would make TOD viable without substantial investment from the public sector (Pojani and Stead, 2014a).…”
Section: Amsterdammentioning
confidence: 99%
“…However, studies to date maintain that TOD is a complex concept, which cannot be easily transferred in its entirety from place to place (Pojani and Stead 2014a). A meta-analysis of 11 international TOD case studies identified 16 critical success factors in TOD implementation, the most significant being: political stability and continuity, relationships between actors in a region, interdisciplinary teams used to implement TOD, and public participation.…”
Section: Brief Review Of Tod Concepts and Issuesmentioning
confidence: 99%